Are sex differences in self‐estimated intelligence an elusive phenomenon? Exploring the role of working memory, creativity, and other psychological correlates in young and older adults. Issue 2 (26th January 2023) - Giannouli, Vaitsa
Abstract: Background: Although there is research examining the demographic predictors of self‐estimated intelligence (SEI) in young adults, so far SEI in old age is little investigated. This study aims to examine the influence of additional variables such as self‐estimated emotional intelligence (SEEQ), physical attractiveness, health, general optimism, religiousness, and working memory (WM) on SEI both in young and older adults. Methods: A total of 159 young (90 women, M age  = 28.77, SD  = 8.83) and 152 older adults (93 women, M age  = 71.92, SD  = 6.84) completed a measure of SEI as well as questions regarding the abovementioned variables. Given that WM is considered a very strong predictor of intelligence, neuropsychological assessment included the measurement of WM and phonologically cued semantic retrieval–verbal storage and processing in WM, as assessed by the Digit Span Forward and Verbal Fluency Task. The visual storage in WM was assessed with a variation of the Visual Patterns Test, and the visual storage and processing in WM with the Corsi blocks task (backward). Positive and Negative Affect Schedule (PANAS‐X) was also administered as a possible influence on cognitive performance and SEI. Results: Young males rated their intelligence quotient (IQ) and emotional quotient (EQ) higher than young females. This was not confirmed for older adults, for which surprisingly the reversed pattern was found. Older women reported higher IQ and EQ than older men. Correlations showed for all participants that the higher they rated their IQ, the higher their ratings of EQ, physical attractiveness, health, and religiousness. No significant correlations between objective tests regarding WM and SEI were found, supporting SEI overestimations. Age, sex, physical attractiveness, and SEEQ were significant predictors of SEI. Discussion: For the first time, a reverse sex difference across age groups in SEI is found. Implications for individuals and healthcare professionals involved in assessment are suggested. Abstract : This research measures self‐estimated intelligence along with other variables for the first time in an extended sample of young and older adults, with an emphasis on old age, as this is an age group so far little investigated. The novelty of this study lies not only in the comparisons of young and older participants, and the cultural context (first study in Greece), but also in the neuropsychological assessment that was performed for the whole sample, as well as the inclusion of relevant correlates of self‐estimated intelligence found in previous published articles.